An Interesting Case Report on Calcaneal Tuberculosis as a Rare Presentation of Disseminated Tuberculosis - Shukor, Ahmad Zulkifli Mohamed; Affandi, Khairunisa Ahmad; Zainulabid, Ummu Afeera (Bangladesh Journal of Infectious Diseases, 2023)
Despite the high prevalence rate of tuberculosis infection in Malaysia, calcaneal tuberculosis (TB) is rare. In this article, we present a case of a 53-year-old Malay female who initially presented with left calcaneal swelling for 3 months. Surgical drainage was performed and affected calcaneal was biopsied for histological examination which findings reported as consistent with tuberculosis infection. Further history revealed concomitant respiratory symptoms with the diagnosis of disseminated TB is supported by positive Mantoux test, detection of Acid-Fast bacilli in sputum and CT imaging showing lung and vertebral involvement. Anti-tuberculosis medication is the first line of treatment in calcaneal TB and surgery is usually reserved for patient with severe, intractable disease. Bangladesh Journal of Infectious Diseases, June 2023;10(1):52-55